Find the complete integral of (x+y)(p+q)^2+(x-y)(p-q)^2=1
To solve differential equation "(x+y)(p+q)^2+(x-y)(p-q)^2 = 1"
Let us put "x+y = X^2" and "x-y = Y^2"
then
"p = \\frac{\\partial z}{\\partial x} = \\frac{\\partial z}{\\partial X}\\frac{\\partial X}{\\partial x}+ \\frac{\\partial z}{\\partial Y}\\frac{\\partial Y}{\\partial x} = \\frac{1}{2X}\\frac{\\partial z}{\\partial X}+ \\frac{1}{2Y}\\frac{\\partial z}{\\partial Y}"
"q = \\frac{\\partial z}{\\partial y} = \\frac{\\partial z}{\\partial X}\\frac{\\partial X}{\\partial y}+ \\frac{\\partial z}{\\partial Y}\\frac{\\partial Y}{\\partial y} = \\frac{1}{2X}\\frac{\\partial z}{\\partial X}- \\frac{1}{2Y}\\frac{\\partial z}{\\partial Y}"
Then
"p+q = \\frac{1}{X}\\frac{\\partial z}{\\partial X}"
and
"p-q = \\frac{1}{Y}\\frac{\\partial z}{\\partial Y}"
Now substitute it in the equation, then we get
"(\\frac{\\partial z}{\\partial X } )^2 + (\\frac{\\partial z}{\\partial Y } )^2 = 1"
Complete integral of the equation is
"z = aX+bY+c" where "a^2 + b^2 = 1"
Put value of X and Y, we get
"z = a\\sqrt{(x+y)} + \\sqrt{1-a^2}\\sqrt{(x-y)} + c"
where a and c are arbitrary constants.
Comments
Leave a comment